2022
DOI: 10.1001/jamanetworkopen.2021.44279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urolithin A Supplementation on Muscle Endurance and Mitochondrial Health in Older Adults

Abstract: IMPORTANCEAging is associated with a decline in mitochondrial function and reduced exercise capacity. Urolithin A is a natural gut microbiome-derived food metabolite that has been shown to stimulate mitophagy and improve muscle function in older animals and to induce mitochondrial gene expression in older humans. OBJECTIVE To investigate whether oral administration of urolithin A improved the 6-minute walk distance, muscle endurance in hand and leg muscles, and biomarkers associated with mitochondrial and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 30 publications
3
98
0
Order By: Relevance
“… 58 Previous data in elderly subjects showed that UA supplementation reduced plasma acylcarnitines. 28 , 29 The current study reproduced these data after long-term administration and in a different population, albeit only at the 500 mg UA dose. These data suggest that the impact of UA on acylcarnitines might be function of the length of intervention and dosing.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“… 58 Previous data in elderly subjects showed that UA supplementation reduced plasma acylcarnitines. 28 , 29 The current study reproduced these data after long-term administration and in a different population, albeit only at the 500 mg UA dose. These data suggest that the impact of UA on acylcarnitines might be function of the length of intervention and dosing.…”
Section: Discussionsupporting
confidence: 74%
“… 33 Acylcarnitines were reduced in the UA 500 mg group and middle- to long-chain acylcarnitines were the most downregulated species ( Figure 3 B), as reported in previous clinical studies. 28 , 29 No changes occurred in the UA 1,000 mg cohort ( Figure 3 B), suggesting a possible time/duration effect of UA on this plasma biomarker.
Figure 3 Effect of Urolithin A on systemic biomarkers of mitochondrial health and inflammation (A) Dose-dependent increase in plasma UA (left), UA-glucuronide (middle), and UA-sulfate (right) plasma levels comparing baseline with the last day of the 4-month treatment period for placebo, UA 500 mg, and UA 1,000 mg doses (n = 27, placebo and UA 500 mg; n = 25, UA 1,000 mg).
…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…To further evaluate the potential of mitochondrial bioenergetics and proteostasis modulation in the treatment of CS in the early stage of the disease we tested the efficacy UA alone or in combination with BZ in a previously described CS zebrafish model ( 45 ). The mitochondrial proteostasis modulator UA was recently characterized and showed no toxicity in a human clinical trial ( 85 87 ). We discovered that UA in combination with BZ synergistically increased the survival of CS embryos and significantly reduced the occurrence of developmental defects.…”
Section: Discussionmentioning
confidence: 99%